SYNTHESIS STRATEGY OF NANOSTRUCTURED TITANIA WITH BCL MORPHOLOGY - VONI STEKY, FRY
TTitanium dioxide (TiO2) is one of semiconductor materials that plays an important role in technological development. One application of TiO2 is as a photocatalyst and catalyst support material. The arrangement of TiO2 morphology is important to support both applications. One of the most interesting morphologies today is the bicontinuous concentric lamellar (bcl) that has been successfully synthesized on silica-based materials. If the morphology is owned by TiO2 then the surface area and its accessibility will increase significantly. Slow hydrolysis is the key in the synthesis stage of monodispersed spherical TiO2 particles from Titanium (IV) Isopropoxide (TTIP) precursors through precipitation in ethanol. Modification of surface morphology of TiO2 particles is carried out by swelling method with ammonia and followed by phase segregation process in solvothermal process that produce particles in bcl morphology. The TiO2 particles of anatase structure with bcl morphology were obtained through calcination at 500 °C for 1 hour. The products of each synthesis stage were characterized using SEM, HRTEM, XRD and Raman spectroscopy. Based on SEM characterization, it is known that the synthesis product has a bcl morphology with particle size of 500-2000 nm. The morphology of this material did not change significantly after the calcination process, but its structure changed from amorph to crystalline anatase polymorphs indicated by XRD and Raman spectra. Through the observation of HRTEM, it appears that the resulting TiO2 particle has a lamellar structure on the surface of the particle, while its center is arranged dense. The transition process from amorphous to anatase is clearly revealed by temperature dependent Raman measurement from 20 to 540 °C, where an amorphous/anatase phase transition occurs over a temperature range of 380-400 °C.